Ornithine decarboxylase gene expression in human lung adenocarcinoma cell (A549) treated with pomegranate juice - Abdul Ghani, Radiah; Nik Abdul Malek, Nik Nurasyikin; Md Yusof, Najwa Farhah; Jamil, Elyna Fatini (Universiti Teknologi Malaysia, 2015)
The polyamine biosynthesis pathway plays a significant role in cell growth, both normal and malignant. As polyamines are crucial in cellular growth and differentiation, they are linked to the development of cancer, with higher polyamine level observed in cancerous cells than in healthy cells. Accordingly, suppressing the polyamine pathway has been found to disrupt tumour development. Chemoprevention is considered a more feasible option in cancer management than chemotherapy, with a focus on natural chemopreventive agent. Pomegranate is known to inhibit several progression of lung cancer, although prior studies on the chemopreventive effect of pomegranate on lung cancer did not explore into polyamine pathway. Hence, this study investigated the effect of pomegranate juice on the polyamine pathway, by focusing on the biosynthesis involving ornithine decarboxylase (ODC), the rate limiting enzyme in the pathway. Quantitative polymerase chain reaction (qPCR) was applied to quantify the changes in ODC gene expression in A549 cells treated with pomegranate. The inhibition of growth was determined using Trypan Blue exclusion and the changes in intracellular polyamine in pomegranate treated cells was observed using High Performance Liquid Chromatography (HPLC). It was found that there was inhibition of A549 cell growth and reduced in intracellular polyamine content in pomegranate treated cells. The ODC expression was significantly inhibited compared to untreated cells, with a 48-fold difference. While this finding supports the hypothesis, there is much yet to be elucidated regarding its exact mechanism.